Effects of red meat, white meat, and nonmeat protein sources on atherogenic lipoprotein measures in the context of low compared with high saturated fat intake: a randomized controlled trial. Issue 1 (4th June 2019) - Bergeron, Nathalie; Chiu, Sally; Williams, Paul T; M King, Sarah; Krauss, Ronald M
ABSTRACT: Background: Dietary recommendations to limit red meat are based on observational studies linking intake to cardiovascular disease (CVD) risk together with the potential of its saturated fatty acid (SFA) content to raise low-density lipoprotein (LDL) cholesterol. However, the relation of white meat to CVD risk, and the effects of dietary protein source on lipoprotein particle subfractions, have not been extensively evaluated. Objective: We tested whether levels of atherogenic lipids and lipoproteins differed significantly following consumption of diets with high red meat content compared with diets with similar amounts of protein derived from white meat or nonmeat sources, and whether these effects were modified by concomitant intake of high compared with low SFAs. Methods: Generally healthy men and women, 21–65 y, body mass index 20–35 kg/m 2, were randomly assigned to 1 of 2 parallel arms (high or low SFA) and within each, allocated to red meat, white meat, and nonmeat protein diets consumed for 4 wk each in random order. The primary outcomes were LDL cholesterol, apolipoprotein B (apoB), small + medium LDL particles, and total/high-density lipoprotein cholesterol. Results: Analysis included participants who completed all 3 dietary protein assignments (61 for high SFA; 52 for low SFA). LDL cholesterol and apoB were higher with red and white meat than with nonmeat, independent of SFA content ( P  < 0.0001 for all, except apoB: red meat compared with nonmeat [ P  = 0.0004]). This was due primarily to increases in large LDL particles, whereas small + medium LDL and total/high-density lipoprotein cholesterol were unaffected by protein source ( P  = 0.10 and P  = 0.51, respectively). Primary outcomes did not differ significantly between red and white meat. Independent of protein source, high compared with low SFA increased LDL cholesterol ( P  = 0.0003), apoB ( P  = 0.0002), and large LDL ( P  = 0.0002). Conclusions: The findings are in keeping with recommendations promoting diets with a high proportion of plant-based food but, based on lipid and lipoprotein effects, do not provide evidence for choosing white over red meat for reducing CVD risk. This trial was registered at Clinicaltrials.gov as NCT01427855.